Enhancement of photo‐conversion efficiency in Cu2ZnSn(S, Se)4 thin‐film solar cells by control of ZnS precursor‐layer thickness. (7th September 2015) - Kim, Gee Yeong; Son, Dae‐Ho; Thi Thu Nguyen, Trang; Yoon, Seokhyun; Kwon, Minsu; Jeon, Chan‐Wook; Kim, Dae‐Hwan; Kang, Jin‐Kyu; Jo, William
Abstract: CZTSSe thin‐film absorbers were grown by stacked ZnS/SnS/Cu sputtering with compound targets, and the precursors were annealed in a furnace with a Se atmosphere. We controlled the thickness of the ZnS precursor layer for the CZTSSe thin films in order to reduce the secondary phases and to improve the performance of the devices. The optimal value of the ZnS precursor thickness was determined for the CZTSSe absorbers, and this configuration showed an efficiency of up to 9.1%. In this study, we investigated the depth profiles of the samples in order to determine the presence of secondary phases in the CZTSSe thin films by Raman spectroscopy and Kelvin probe force microscopy. Cu2 SnSe3, ZnSe, and MoSe2 secondary phases appeared near the back contact, and the work function distribution of the CZTSSe thin‐film surface and the secondary phase distribution were different depending on the depths of the absorber layer. This phase characterization allows us to describe the effects that changes in the thickness of the ZnS precursor can have on the performance of the CZTSSe thin‐film solar cells. Although it is important to identify the phases, the effects of secondary phases and point defects are not yet fully understood, even in optimal devices. Therefore, phase identification that is based on the work function and the results obtained from the Raman spectra in terms of the depth profile are instrumental to improve the surface and interface of CZTSSe thin‐film solar cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The optimal value of the ZnS precursor thickness was determined for the CZTSSe (9.1%). Depth profiles of the samples to determine the presence of secondary phases in the CZTSSe. Phase identification is instrumental to improve the surface and interface of CZTSSe cells.